1996
DOI: 10.1021/bi952107i
|View full text |Cite
|
Sign up to set email alerts
|

β-Secondary and Solvent Deuterium Kinetic Isotope Effects on β-Lactamase Catalysis

Abstract: Beta-Secondary and solvent deuterium kinetic isotope effects have been determined for the steady-state kinetic parameters V/K and V for turnover of a depsipeptide substrate, m-[[(phenylacetyl)glycyl]-oxy]benzoic acid, and of a beta-lactam substrate, penicillanic acid, by three typical class A beta-lactamases and a class C beta-lactamase. The isotope effects on alkaline hydrolysis of these substrates have been used as a frame of reference. The effect of the transition state conformation of the substrates in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 57 publications
9
59
0
Order By: Relevance
“…Fits of the data points yielded equivalent, small solvent kinetic isotope effects of 1.4 ± 0.1 on V and V/K (Table 1). The small effects on nitrocefin hydrolysis by BlaC are similar to those observed previously for penicillins and cephalosporins by Hardy & Kirsch (1.53 and 1.09, respectively) and Adediran & Pratt (1.04 and 1.39, respectively) (22, 30). Since k cat / K m only reports on steps between binding of nitrocefin to the free enzyme, and the formation of the covalent acyl-enzyme, the steady-state results for nitrocefin hydrolysis revealing equivalent, small solvent KIEs on k cat / K m and k cat supports acylation as the rate-limiting step for this substrate.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Fits of the data points yielded equivalent, small solvent kinetic isotope effects of 1.4 ± 0.1 on V and V/K (Table 1). The small effects on nitrocefin hydrolysis by BlaC are similar to those observed previously for penicillins and cephalosporins by Hardy & Kirsch (1.53 and 1.09, respectively) and Adediran & Pratt (1.04 and 1.39, respectively) (22, 30). Since k cat / K m only reports on steps between binding of nitrocefin to the free enzyme, and the formation of the covalent acyl-enzyme, the steady-state results for nitrocefin hydrolysis revealing equivalent, small solvent KIEs on k cat / K m and k cat supports acylation as the rate-limiting step for this substrate.…”
Section: Resultssupporting
confidence: 87%
“…Solvent kinetic isotope effects are powerful probes of proton transfer events in enzyme-catalyzed reactions and have been used to probe transition state structures for both acylation and deacylation reactions of mechanism-related proteases (2528). This extends to the analysis of SKIEs on β -lactamases, including important contributions on penicillanic acid sulfone hydrolysis by Brenner & Knowles (29), β -lactam hydrolysis by the Bacillus cereus TEM β -lactamase by Hardy & Kirsch (22) and β -lactam hydrolysis by several related class A and C β -lactamases by Adediran & Pratt (30). We chose three substrates for this analysis with BlaC, which span nearly five orders of catalytic turnover rates.…”
Section: Resultsmentioning
confidence: 77%
“…3D). Previous kinetic isotope effect (KIE) studies and QM/MM calculations suggest that the formation of the tetrahedral transition state is the rate-limiting step of the acylation reaction during Class A β-lactamase catalysis 26,36 . More specifically, general base catalysis is required to initiate the formation of this tetrahedral TS, whereas general acid catalysis is involved in the collapse of the TS.…”
Section: Resultsmentioning
confidence: 99%
“…The C-7 carbonyl of avibactam was positioned within the oxyanion hole formed by residues Ser64 (2.9 Å) and Ser318 (3.0 Å). We recognize that the general base involved in the acylation of avibactam is debated for class C ␤-lactamases (32); Tyr150 and Lys67 are hypothesized to be involved in the deprotonation of Ser64 (33)(34)(35)(36)(37)(38)(39)(40). The molecular representation generated here revealed that both Tyr150 (3.0 Å) and Lys67 (2.8 Å) can form hydrogenbonding interactions with the hydroxyl side chain of the nucleophilic residue Ser64, suggesting that either residue may be involved in the acylation mechanism of avibactam.…”
Section: Resultsmentioning
confidence: 99%